Evaluation of the quality of contracted family doctor services based on patient perceptions and expectations: a follow-up analysis from the elderly with chronic diseases in rural Jiangsu, China. Issue 12 (23rd December 2021) - Jin, Shengxuan; Wang, Zhonghua; Tian, Lanlan; Sun, Zhenyu; Lin, Zhenping; Qian, Dongfu
Abstract : Introduction: The policy focus of contracted family doctor services (CFDS) has been shifting to improve quality and efficiency in China. The study's objective was to establish a quality evaluation scale for CFDS based on the perceived service quality model and to assess the service quality from the perspective of patient perceptions and expectations. Methods: Data were obtained from a 2-year follow-up survey of CFDS in Jiangsu, China. A total of 1264 elderly people with chronic diseases were tracked. The self-developed scale was designed based on the perceived service quality model. The product scale method was used to assign weighted values, the Wilcoxon signed-rank test was used to compare the differences over the 2 years, and pooled cross-sectional regression was conducted to evaluate the associated factors with the gap scores of service quality. Results: There were significant differences between perceptions and expectations in each dimension in the 2 years (p<0.05), and the service quality gaps existed. Over the 2 years, Accessibility and Horizontal continuity were the first-ranked and second-ranked in expectations; the top three scores in perception were Horizontal continuity, Comprehensive service and Accessibility dimensions. The service quality gap in 2020 was smaller than that in 2019 (p<0.05). There were differences in the perception scores in the Vertical continuity, Technical and Economic dimensions and in the expectation scores in the Horizontal continuity, Vertical continuity and Technical dimensions between the 2 years (p<0.05). The factors that were significantly associated with each dimension score included the Jiangsu region, gender, age and education levels (p<0.05). Conclusion: The quality evaluation scale of CFDS has good reliability and validity. Policy efforts should be focused on accelerating the development of medical alliances, optimising medical insurance policies and improving the capacity of family doctor services to meet the needs of the elderly with chronic diseases.